Breast Cancer, Chemokines, And Metastasis: A Search for Decoy Ligands of the CXCR4 Receptor - Gerald J. Mizejewski (Journal of Neoplasms, 2018)
Breast cancer (BC) is the leading cause of cancer-related deaths in young to middle-aged women worldwide. Moreover, the survival rate in BC-patients is only 20% when associated with metastatic disease. The high mortality rate observed in BC women with metastatic disease has precipitated a major challenge revealing an unmet need to develop new therapeutic strategies in treating metastatic cancer. One such approach has involved utilization of chemokines and their receptors as therapeutic targets for cancer metastasis. It has been established that a definitive correlation exists between overexpressed CXCR4 malignant cell receptors and cancer cell growth, invasion, and migration. It is also widely accepted that the CXCR4 receptor, complexed to its CXCL12 ligand, plays a major role in establishing migratory pathway gradients for cancer cells migrating to distant tissues/organ sites. It would follow that chemokine decoy ligands, such as peptide antagonists and inhibitors, could serve to induce receptor blockade and impede subsequent intracellular signaling. Such ligands, synthetic and natural, reportedly contribute to reducing cancer cell growth, invasion, adherence, and migration. The present commentary describes several existing synthetic CXCR4 receptor-ligand peptide antagonists and presents a strategy to develop naturally-occurring human protein-derived peptide candidates.
Keywords: Alpha-fetoprotein